Investigating the implementation of English-Huffaz Program for preschools - Zuraina, Ali (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The study explores the implementation of a program namely English-Huffaz among preschoolers in their early years of education. It is a program that introduces the memorization of selected verses of the al Qur’an besides promoting the learning of English language among preschoolers that are from four (4) to six (6) years old. The study that employs qualitative data inquiry; in particular semi-structured interviews, gathers information from two (2) teachers pertaining to the implementation of teaching hafazan and English in one of the preschools in the district of Pahang, East Coast of Malaysia. Seven (7) themes emerge after data are analyzed employing inductive analysis. Findings that are obtained from the study are significant especially to Muslim parents who have the intention to prepare their children for the latter formative years of education; both for the needs of herenow and hereafter